Pengaruh Gaya Kepemimpinan Kepala Sekolah dan Motivasi Kerja terhadap Kepuasan Kerja Guru pada Sekolah Dasar Negeri 112/1 Perumnas Kecamatan Muara Bulian Kabupaten Batang Hari - Nadiatul Khoiroh (Universitas Batanghari Jambi, 2019)
The tiitle of this research is The Influence of Head School Leadership And Work Motivation On Teacher Work Satisfaction In Public Elementary School 112/1 Perumnas Sub-district of Muara Bulian, Batang Hari Regency. Testing is done using multiple linear regression analysis. Hypothesis testing is done by using t test and F test. The magnitude of the effect is known through testing the Path analysis. Based on the discussion it can be concluded that the effect of Leadership (X1) and Motivation (X2) together on Job Satisfaction (Y) is 53.547%. In the t test, the effect of Leadership (X1) and Motivation (X2) has a partial effect on Job Satisfaction (Y). in the F test, Leadership (X1) and Motivation (X2) has a simultaneous influence on Job Satisfaction (Y).